Race and reunion: the Civil war in American memory - Blight, David W.
Arguably, no historical event has left an impression on America´s collective psyche as the Civil War. In the war´s aftermath, Americans had to both hold on to as well as cast off a harrowing past. David Blight explores the dangerous path of remembering and forgetting, and exposes its costs vis-à-vis race relations and America´s national reunion. In 1865, faced with a devastated landscape and a splintered America, the North and South commenced on the path to a slow and painful process of reconciliation. The resulting decades saw the victory of the mindset of reunion. Race and Reunion is a narrative of how the concord of white America was bought through the growing separation of black and white memory of the Civil War. Blight investigates the shifting significance of death and sacrifice, Reconstruction, the romanticized South of literature, reminiscences of battle, the idea of the Lost Cause, and the ritual of Memorial Day. Blight resurrects the variety of African-American voices and memories of the war and the efforts to preserve the emancipationist legacy in the midst of a culture built on its denial. What does the Civil War mean? What did it mean to those fighting it, surviving it and recalling it as a personal experience? Moreover, what did it mean to the veterans´ children and grandchildren? Along with these important questions, Blight also asks what the Civil War meant (or did not mean) vis-à-vis the larger American social and political memory as a function of what it meant on a personal level. In a deep and apparently comprehensive handling of the a variety of viewpoint held in the half-century following Lee´s surrender at Appomattox, Race and Reunion is a lesson to the reader of the complex nature of collective memory.